The Sahta Method: A Learning Innovation To Improve Nahwu Comprehension For Junior High School Students - Wildan Azzam Firdausi; Talqis Nurdianto; Mohamad Nor Amin Samsun Baharun (South Sulawesi Education Development (SSED), 2025)
Learning nahwu is often considered difficult and tedious, especially for junior high school students in a pesantren environment. This study aims to examine the application of the SAHTA (Sahlan wa Tafrihan) method, a song-based nahwu learning method, in improving students' understanding of nahwu. This research uses a mixed method with an exploratory sequential design, starting with a qualitative approach through in-depth interviews with the inventor of the SAHTA method and nahwu teachers at the ALMATERA Islamic Boarding School to explore the implementation of the SAHTA method. The quantitative approach was carried out on 55 grade 9 students of MTs ALMATERA who had attended nahwu learning for two years, selected using a purposive sampling technique. Quantitative data were obtained through questionnaires and then analyzed using IBM SPSS Statistics 25 through assumption tests (normality and linearity) and hypothesis testing (Pearson correlation). The analysis results show that the SAHTA method is applied through fun stages such as singing, modeling, practice, and vocabulary reinforcement. Based on the Pearson correlation test, a positive and significant relationship was found between using of the SAHTA method and students' understanding of nahwu (r = 0.543; p < 0.05). This finding shows that the SAHTA method is effectively used as an alternative to learning nahwu because it can improve students' understanding in a fun and contextual way.